2019
DOI: 10.15406/hij.2019.03.0012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different media on the growth and yield of Swiss chard (Beta vulgarisvar. cicla) grown in hydroponics

Abstract: Decline in the availability of suitable land and good fertile soil for vegetable production due to climate change, urbanisation and increasing population has resulted in studies to find alternative media that can be used to grow high value crops such as Swiss chard. The experiment was conducted at the Horticulture Department Greenhouses of the University of Eswatini, Luyengo Campus to determine the growth and yield of Swiss chard using different growing media. The treatments were laid out in a Randomised Compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The crop yield of both species, also when grown in diluted seawater with 1 mM of N-NO 3 − , remained greater than the productions of leaves that were reported for B. vulgaris [16,36,37] and Spinacia oleracea [16], cultivated under greenhouse in hydroponics with standard nutrient solutions (the results of these studies are summarized in Table S5). Pantanella [19] reported that SB that was grown in saltwater (10 ppt) aquaponics yielded 2.6 kg m −2 in four weeks.…”
Section: Crop Yield and Mineral Uptakementioning
confidence: 72%
See 1 more Smart Citation
“…The crop yield of both species, also when grown in diluted seawater with 1 mM of N-NO 3 − , remained greater than the productions of leaves that were reported for B. vulgaris [16,36,37] and Spinacia oleracea [16], cultivated under greenhouse in hydroponics with standard nutrient solutions (the results of these studies are summarized in Table S5). Pantanella [19] reported that SB that was grown in saltwater (10 ppt) aquaponics yielded 2.6 kg m −2 in four weeks.…”
Section: Crop Yield and Mineral Uptakementioning
confidence: 72%
“…The K/Na molar ratio is also shown. Table S5: Leaf production of some vegetable species that are grown hydroponically under greenhouse conditions [16,36,37]. Table S6: Health risk index (HRI, %) associated with the consumption of 100 g FW of leaves of Swiss chard and sea beet plants that are grown hydroponically with different concentrations of the sea salt Instant Ocean (IO; 0 and 10 g L −1 ) and nitrate (N-NO 3 − ; 1 and 10 mM) in the nutrient solution (see Table 2 for abbreviations).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…En el número de hojas existió diferencia favorable de AP+F de 40% con respecto a ECR. ECR presentó un promedio de hojas, comparado con otros autores que reportan 7 y 8.7 como promedio en un sistema de hidroponía, por lo que el valor de ECR se considera adecuado (Ube, 2014 2 ; Delgado-Zambrano, 2016 3 ; Hlophe et al, 2019); aunque el número de hojas en ECR fue menor que en AP+F la cantidad de la biomasa fresca en ECR fue de 161.61 gramos, esta diferencia puede estar asociada a la presencia de microorganismos en el sistema; Venegas-González y colaboradores en el 2019, emplearon inoculantes microbianos (Bacillus subtilis y Trichoderma harzianum) en la producción de acelga, demostraron un incremento en el crecimiento y la producción de las plantas asociada a la absorción nutrimental del sustrato, lo cual se reflejó en la biomasa fresca (tamaño y numero de hojas) (Venegas-González, et al, 2019).…”
Section: Resultados Y Discusiónunclassified
“…It it worth noting that crop cultivation has over time heavily relied on conventional agricultural practices which unfortunately has stimulated the emission of major greenhouse gases (GHGs) like Nitrous oxide (Di Benedetto et al, 2017). Accompanying this, is the deterioration in arable land because of industrialization, urbanization and increase in population (Hlophe et al, 2019;mgbemene et al, 2016) especially in African urban settings.…”
Section: Introductionmentioning
confidence: 99%